Clyra Evera / Natalia Arwina Abdul Rashdee ... [et al.]. - Abdul Rashdee, Natalia Arwina; Mohd Johan, Nurkhalieda; Masrul Nizam, Nur Alisha; Shahrul Azhar, Nuralyaa Aqilah; Othman, Muhamad Akimi (2025)
Clyra Evera is a partnership firm with its premise at Unit B-G-12, Tamarind Square, Persiaran Multimedia, Cyberjaya, 63000 Selangor, Malaysia, while its correspondence address is at P.O. Box 4567, 63007 Cyberjaya, Selangor, Malaysia. Manufacturing and selling quality lifestyle products that are eco-friendly, such as customized tote bags, among others, is an important way of meeting the demand for a stylish and sustainable living. It will combine "quality craftsmanship, innovative design, and environmentally friendly practices to ensure both functional and stylish products" for delivery. Objectives that would guide Clyra Evera include production of quality products, creating sustainable businesses, meeting the needs of diverse consumers, and building a brand that is trustable in the eco-friendly market. The key products and services sold by Clyra Evera are customized tote bags, among other lifestyle products, made to the liking of a person. Target customers are young working professionals, corporate clients, and students who give considerable importance to sustainability and customization while making purchases.